Health risk assessment of trace elements in the Tonle Sap Great Lake and the Tonle Sap River in Cambodia during the rainy season - Kongkea Phan; Kyoung-Woong Kim (IWA Publishing, 2023)
To investigate the potential health risk of trace elements in the Tonle Sap Great Lake system, lake (n = 37) and river (n = 14) water samples were collected and analyzed for 19 trace elements (Ag, Al, As, B, Ba, Cd, Co, Cr, Cu, Fe, Ga, Mn, Mo, Ni, Pb, Se, Tl, U and Zn) using inductively coupled plasma mass spectrometry. As a result, Cd was not detected in any river and lake water samples. Al, Fe and Mn in lake water exceeded the regulation limits of Cambodia, USEPA and WHO. Health risk assessment using the USEPA model indicated that male and female Cambodian residents are at minimal risk of non-carcinogenic effects from single and mixed trace elements through lake and river water consumption. Nevertheless, As, Tl, Co, Ba, Mn and Cr might pose high potential health risks to consumers which requires more attention. Therefore, regular monitoring and further studies are required to investigate the pollution trends and toxic behavior of these trace elements in the Tonle Sap Great Lake system. HIGHLIGHTS We investigated the distribution of 19 trace elements in the Tonle Sap Great Lake system.; As, B, Cu, Mo, Ni, Se and U in the Great Lake were higher than those in the river.; Ag, As, B, Ba, Cu, Ga, Mn and Se were significantly different among the five provinces.; Residents did not have the non-carcinogenic effect of trace elements through lake and river water consumption.;